In search of new facts: interwar Japanese military intelligence activities in the Baltic states and Finland: 1918–1940 - Masunaga, Shingo (fi=Turun yliopisto|en=University of Turku|, 2021)
This thesis is the world’s first ever academic work clarifying the interwar Japanese military intelligence activities in the Baltic Sea region. These activities can be divided into three periods: 1) Planning and Research (1919–1931), 2) Nurturing Friendships (1932–1937), and 3) Joint Intelligence Operations (1937–1940). In the first period, the Japanese Army estimated the effects of the intelligence activities in the region, mainly against the Soviet Union. There were several Japanese Army officers such as Captain Komatsubara and Major Obata stationed in Tallinn to observe the Soviet political situation. And, as tensions between Japan and the Soviet Union rose in the early 1930s, the Japanese Army formulated a special guideline to initiate the regional intelligence operation in 1932. In this ‘Plan of 1932’, Estonia and Finland were named as potential hubs for Japanese intelligence activities. According to the plan, the Japanese sent student officers to the both countries, and also to Latvia, to nurture friendships with the Japanese Army. In the late 1930s, the situation surrounding the Plan of 1932 saw a drastic change in terms of Japanese diplomatic relations with China and the Soviet Union. The plan became a more aggressive ‘espionage offensive’ against the Soviet Union while promoting Japanese righteousness in the Second Sino-Japanese War (1937–45). In 1938, a new guideline for the Japanese Army’s foreign intelligence operations was formulated. In this Plan of 1938, the Japanese attempted to gain a decisive victory against the Soviet Union through various stratagems. However, their intelligence operations, jointly organised by the Estonian and German intelligence services probably failed, and in consequence they did not affect the international political situation of the late 1930s.

Tämä opinnäyte on maailman ensimmäinen akateeminen työ, joka selkeyttää Japanin sotienvälisiä sotilastiedustelutoimintaa Itämeren alueella, erityisesti Baltian maissa ja Suomessa. Tuona aikana japanilaisten alueella toiminta voidaan jakaa kolmeen jaksoon: 1) suunnittelu ja tutkimus (1919–1931), 2) ystävyyden vaaliminen (1932–1937) ja 3) yhteiset tiedustelutoimet (1937–1940). Ensimmäisellä ajanjaksolla Japanin armeija arvioi alueen tiedustelutoiminnan vaikutuksia pääasiassa Neuvostoliittoa vastaan. Tallinnaan oli sijoitettu useita Japanin armeijan upseereita, kuten kapteeni Komatsubara ja majuri Obata tarkkailemaan Neuvostoliiton poliittista tilannetta. Ja koska Japanin ja Neuvostoliiton väliset jännitteet olivat kasvaneet 1930-luvun alkupuolella, Japanin armeija laati erityisen ohjeen alueellisen tiedustelutoiminnan aloittamiseksi vuonna 1932. Vuoden 1932 suunnitelmassa Viro ja Suomi nimettiin potentiaalisiksi keskuksiksi Japanin tiedustelutoimintaan. Suunnitelman mukaan japanilaiset lähettivät opiskelijaupseereja molempiin maihin ja myös Latviaan edistämään ystävyyttä Japanin armeijan kanssa. 1930-luvun lopulla vuoden 1932 suunnitelmaan liittyvä tilanne muuttui dramaattisesti Japanin diplomaattisissa suhteissa Kiinan ja Neuvostoliiton kanssa. Suunnitelmasta tuli aggressiivisempi painotuksenaan ”vakoiluhyökkäys” Neuvostoliittoa vastaan edistäen samalla japanilaisten vanhurskautta toisessa Kiinan ja Japanin sodassa (1937–45). Vuonna 1938 laadittiin uusi ohje Japanin armeijan ulkomaan tiedusteluoperaatioille. Japanilaiset yrittivät tässä vuoden 1938 suunnitelmassa saavuttaa ratkaisevan voiton Neuvostoliittoa vastaan eri juonien avulla. Heidän Viron ja Saksan tiedustelupalvelun yhdessä järjestämät tiedusteluoperaatiot kuitenkin ilmeisesti epäonnistuivat, joka seurauksena suunnitelma ei lopulta vaikuttanut 1930-luvun lopun kansainväliseen poliittiseen tilanteeseen.